Agile fusion method for the determination of Pu isotopes in diverse sediments. (October 2021) - Cook, Megan
Abstract: Atmospheric nuclear testing has occurred worldwide resulting in trace amounts of plutonium (Pu) isotopes in soils and sediments across the globe. Soils and sediments can vary greatly in both physical and chemical properties within close geographic regions presenting a major challenge for sample preparation in the analysis of fallout radionuclides. It is vital to have a rapid, agile method for the complete digestion of samples containing refractory Pu particles to address this challenge. A radioanalytical procedure for the analysis of Pu isotopes in soils/sediments has been developed improving sample preparation using fusion. This is done by eliminating the need for pre-dissolution combustion to remove organic material and providing greater application to a diverse range of samples including those of metal-bearing mineralogy. The integration of borate and peroxide flux materials creates a sample dissolution procedure that is greater than the sum of its parts. This method is applicable to the analysis of 239/240 Pu in soil/sediment samples with a sample mass of 3 g, ranging from 0.05 to 5000 mBq/g achieving 242 Pu tracer recoveries between 50 and 94%, with a trace-level detection limit of 0.04 mBq/g and measurement uncertainties down to 19%; adjustable to measurement priorities with variation in count time, background counts, chemical recovery and total activity of the sample. This sample preparation technique can be utilized with complementary analysis of alpha spectrometry or ICP-MS. Achieving these parameters provides a highly adaptable standard method for 239/240 Pu in soil/sediment analysis applicable to samples from radioecological research at trace environmental levels to emergency response scenarios with 48-h turn-around producing highly repeatable, succinct and high-quality analysis. Highlights: An agile method for the analysis of refractory Pu particles in soils/sediments removing the need for pre-dissolution combustion. Applicable to a diverse range of samples including metal-bearing mineralogy. Validated for a range of 239/240 Pu contamination (0.1–5000 mBq/g) achieving tracer recoveries between 50 and 94%, and a detection limit of 0.107 mBq/g using a combination of certified reference materials and real samples. Highly adaptable method of analysis applicable to radioecological research at trace environmental levels and emergency response scenarios with 48-h turn-around producing highly repeatable, succinct and high-quality analysis.